Rebellion Of Osvald Alving Reflected In Henrik Ibsens Ghosts Drama (1881): Psychoanalytic Approach - Anoraga, Ananda Dhira; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.S. M. Hum (2016)
The problem of this study is How is the rebellion reflected at Henrik Ibsen's ghosts drama?". The objective of this study to analyze Ghosts based on Structural analysis and the to analyze Ghosts play based on Psychoanalytic perspective. The researcheremploys qualitative method. The writer uses two data sources: primary and secondary. The primary data source is about The primary data sources is the textplay itself. Then, the secondary data sources are from other sources such as essay, articles, biography of Henrik Ibsen, Internet and other relevant information.The method of data collection is library research and the technique of data collection is descriptive technique. Based on the anaylisis, the researcher get some onclusions. The study showsthat the problem faced by the minor character is his own rebellion. Oswald is presented by Henrik Ibsen, the author of Ghosts .Oswald is from Norway but lives in Paris. Oswald's is an artist, becausehe fearing that his exuberance and creativity would dissipate like that his father, he wanted to leave his home in Norwey and he wanted to stay in Paris with Regina.The mistake is Oswald's live as an artist that caused him trapped in drugs abuse, alcohol, and having free sex.Thejoy of life as an artist in Paris and from his father make him infected syphilis.